Efectiveness of Cooperative Learning Model Type Learning Together (LT) on Learning Outcomes and Creativity of Students on Acid-Base Material - Setia Rahmawan; Elisa Yuliana (Universitas Tidar, 2023)
This study aims to determine the effectiveness of Learning Together (LT) type cooperative learning model on learning outcomes and creativity of students on acid-base material in class XI MIPA SMA Muhammadiyah 3 Yogyakarta. The population of this study were all students of class XI MIPA SMA Muhammadiyah 3 Yogyakarta which amounted to 93 students and divided into 3 classes, namely class XI MIPA 1, XI MIPA 2, and XI MIPA 3. The samples of this study were class XI MIPA 2 as the control class and class XI MIPA 3 as the experimental class, each class consisting of 31 students. This research method is a quasi-experiment. The design used is nonequivalent control group design. Data collection techniques using test questions and filling out questionnaire sheets of students’creativity. Data analysis techniques used are normality test, homogeneity test, and hypothesis testing (Mann Whitney test and independent sample t-test). Based on the results of the Mann Whitney test analysis, the Sig (2-tailed) value of 0.000 <0.05 was obtained, so H0 rejected and H1 was accepted, meaning that the Learning Together (LT) type cooperative learning model was effective on learning outcomes on acid-base material. Based on the results of the independent sample t-test analysis, the Sig. 0.005 < 0.05, so that H0 rejected and H1 was accepted, meaning that the Learning Together (LT) type cooperative learning model is effective on students' creativity in acid-base material.